2013
DOI: 10.3906/biy-1211-17
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate (Punica granatum L.) reduces endoplasmic reticulum stress induced by renal ischemia/reperfusion injury in rat

Abstract: Ischemia/reperfusion (I/R) is one of the main causes of acute renal failure, leading to generation of reactive oxygen species (ROS) and ensuing oxidative stress, which results in unfolded/misfolded protein accumulation and its dependent response pathways, generally known as unfolded protein response (UPR), in the endoplasmic reticulum (ER). We studied the effects of renal I/R on the expression of ER-stress genes, as well as concomitant effects of oral pretreatment with pomegranate (Punica granatum L.) pith and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These components have antioxidant and anti‐inflammatory activities and ameliorated hexachlorobutadiene‐induced nephrotoxicity. Oral pretreatment with pomegranate can reduce ischemia–reperfusion‐induced injury in kidneys via antioxidant defense mechanisms (Hashemi et al, ). Pomegranate extract has also shown protective effects on ischemia–reperfusion‐induced ARF (Sancaktutar et al, ).…”
Section: Natural Medicine Effective On Arf Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These components have antioxidant and anti‐inflammatory activities and ameliorated hexachlorobutadiene‐induced nephrotoxicity. Oral pretreatment with pomegranate can reduce ischemia–reperfusion‐induced injury in kidneys via antioxidant defense mechanisms (Hashemi et al, ). Pomegranate extract has also shown protective effects on ischemia–reperfusion‐induced ARF (Sancaktutar et al, ).…”
Section: Natural Medicine Effective On Arf Modelsmentioning
confidence: 99%
“…Thus, this effect of proanthocyanidins could be considered in the therapy of myoglobinuric ARF (Stefanovic et al, 2000). (Hashemi et al, 2013).…”
Section: Vitis Viniferamentioning
confidence: 99%
“…In contrast, an increase in ALP activity and bilirubin level reflect the pathological alteration in biliary flow, increase in serum total bilirubin and direct bilirubin concentration after paracetamol administration might be attributed to normal uptake ,conjugation and excretion by the damage hepatic parenchyma (Wang et al, 2008). Significant decrease in total protein, albumin and globulin due to disorder in synthetic function of liver (Ogutcu et al, 2008) our results referred that Cupressus sempervirens improve the level of serum total protein ,albumin and globulin due to high polyphenolic content ,thus antioxidant properties of this plant due to its capacity to restore the functionality of the hepatic cell and reduce endoplasmic reticulum oxidation stress (Hashemi et al, 2013), globulin improvement may be due to its immune stimulatory effect (Ross and Pawlina, 2011). Our study showed that paracetamol toxicity induced hypercholesterolemia with increased triglycerides and (LDLC) and reduced (HDLC).…”
Section: Discussionmentioning
confidence: 64%